MicroRNA transcriptome analysis on hypertrophy of ligamentum flavum in patients with lumbar spinal stenosis - Mori, Taiki (Spine Surg Relat Res, 2017)
INTRODUCTION: Molecular pathways involved in ligamentum flavum (LF) hypertrophy are still unclarified. The purpose of this study was to characterize LF hypertrophy by microRNA (miRNA) profiling according to the classification of lumbar spinal stenosis (LSS). METHODS: Classification of patients with LSS into ligamentous and non-ligamentous cases was conducted by clinical observation and the morphometric parameter adopting the LF/spinal canal area ratio (LSAR) from measurements of magnetic resonance imaging (MRI) T2 weighed images. LF from patients with ligamentous stenosis (n=10) were considered as the degenerative hypertrophied samples, and those from patients with non-ligamentous LSS (n=7) and lumbar disc herniation (LDH, n=3) were used as non-hypertrophied controls. Profiling of miRNA from all samples was conducted by Agilent microarray. Microarray data analysis was performed with GeneSpring GX, and pathway analysis was performed using Ingenuity Pathway Analysis. RESULTS: The mean LSAR in the ligamentous group was significantly higher than that in the control group (0.662±0.154 vs 0.301±0.068, p=0.0000171). Ten significantly differentially expressed miRNA were identified and taken as a signature of LF hypertrophy: nine miRNA showed down-regulated expression, and one showed up-regulated expression in the ligamentous LF. Among those, miR-423-5p (r(s)=-0.473, p<0.05), miR-4306 (r(s)=-0.628, p<0.01), miR-516b-5p (r(s)=-0.629, p<0.01), and miR-497-5p (r(s)=0.461, p<0.05) were correlated to the LSAR. Pathway analysis predicted aryl hydrocarbon receptor signaling (p<0.01), Wnt/β-catenin signaling (p<0.01), and insulin receptor signaling (p<0.05) as canonical pathways associated with the miRNA signature. CONCLUSIONS: Classification based on quantification of the MRI axial image is useful for studying hypertrophy of the LF. Aryl hydrocarbon receptor and Wnt/β-catenin signaling may be involved in LF hypertrophy.